An Autonomous Agriculture Robot Using IoT - Joseph, Linta; Joseph, Sara; H, Sarath; Abraham, Shibino P; George, Anish (International Journal of Computer Sciences and Engineering, 2020)
About 40 percent of the world’s population relies on the agriculture field. Apart from traditional farming, recent years have demanded the application of autonomous vehicles in agriculture. The proposed system aims at designing an autonomous agricultural robot that can be controlled through IoT providing real-time monitoring of the field thereby improving the irrigation system. The system can be controlled by an IoT module. The proposed system aims at reducing the human intervention in farms providing sufficient environmental conditions for the crops with ensuring proper irrigation and efficient utilization of resources. This Agribot can perform the basic functions like monitoring, taking soil parameters, and control the irrigation system accordingly. These robots have a major role in precision farming. The application helped increase investment and using these in real-time. Precision agriculture thus improves agricultural yield and takes precautions in environmental risks demanding the need for agricultural robots. Hence autonomous IoT based agricultural robots are designed to perform the basic elementary functions required to be carried out in fields.